Design and development of non‐perfluorinated ionic polymer metal composite‐based flexible link manipulator for robotics assembly. Issue 7 (2nd November 2018) - Jain, Ravi Kant; Khan, Ajahar; Inamuddin; Asiri, Abdullah M.
Abstract : In this article, a noble ionic polymer metal composite (IPMC) based on sulfonated polyvinyl alcohol (SPVA) and 1‐ethyl‐3‐methylimidazolium tetrachloro aluminate (IL) with deposited Pt was fabricated and used to develop flexible link manipulator. The proposed IPMC was fabricated by simple solution casting method using SPVA and IL with deposited Pt metal by electroless plating method. Herein, SPVA polymer membrane acts as a medium for metal ion migration, and the Pt act as the surface conductive electrode on both sides of the membrane surface. Experimental characterizations such as scanning electron microscopy, cyclic voltammetry and linear sweep voltammetry, load characterization, and actuation performance confirm the excellent electrochemical and electromechanical response as compared with the other reported IPMCs. This method of fabrication exhibits significant advantages, such as the easy process of fabrication using non‐toxic materials. A two‐link flexible manipulator was developed, where the electromechanical behavior of polymer‐based actuator provides an important step for robotic assembly. This shows the potential of flexible compliant fingers and joints in flexible link manipulator for robotic assembly. POLYM. COMPOS., 40:2582–2593, 2019. © 2018 Society of Plastics Engineers